ECONOMETRIC ANALYSIS OF THE RELATIONSHIP BETWEEN RENEWABLE AND NON-RENEWABLE ENERGY CONSUMPTION WITH ECONOMIC GROWTH IN INDONESIA - KORRA HERDYANTI (NIM : 22114025), MIXSINDO
Energy consumption has an impact to Indonesia's economic growth. The energy consumed in Indonesia is largely sourced from fossil energy and renewable energy in small quantities. This study will look at the relationship between energy consumption and economic growth with capital and labor as another variable that has an effect on GDP. To examine the relationship between variables, a Granger causality test was conducted. The test results state that the oil, gas and renewable energy consumption have a bi-directional causality relationship with economic growth or meet the feedback hypothesis. Coal consumption has a unidirectional causality to economic growth or meets growth hypothesis. Econometric modeling using ARDL method was conducted to be able to identify the short and long-term relationship. The result is there is a long-term relationship between energy consumption, capital and labor to economic growth. And also from the model the contribution of variable energy consumption, capital and labor to economic growth in Indonesia will be shown. The ARDL model will be used for forecasting until 2025. The forecast result will show if the target of energy mix prepared by the government until 2025 has been able or not to achieve the target of economic growth.has been able to achieve the target of economic growth. Based on the research, energy mix scenarios to achieve the target of economic growth are the proportion of 29% natural oil, 20% natural gas, 40% coal and 11% EBT with constant capital growth of 12,2% per year and the average increase in the labor force amount 2% per year.